The Relationship between Social Support and Burnout in Employee X at Y Ltd Palembang - Fadly Ramadhan; Desy Arisandy (Global Writing Academica Researching & Publishing, 2023)
This study aims to determine the relationship between social support and burnout on Employee X at Y Ltd Palembang. The hypothesis put forward in this study is that there is a very significant relationship between social support and burnout for Employee X at Y Ltd Palembang. The total population in this study was 219 X employees who were used as samples. The sampling technique using simple random sampling technique. Measuring tools used in this study is the scale of burnout and social support. The analysis technique used a simple regression analysis technique with the help of SPSS version 20. The results of research data analysis with a computer using the SPSS version 20 for windows program, showed a correlation coefficient (r) of 0.386, a coefficient of determination (R Square) of 0.157, and a value of p = 0.000. The results of the analysis obtained show that there is a very significant relationship between social support and burnout for Employee X at Y Ltd Palembang of 15.7%.